2014
DOI: 10.1513/annalsats.201308-266oc
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Clarithromycin and Ethambutol for Mycobacterium avium Complex Pulmonary Disease. A Preliminary Study

Abstract: This preliminary study suggests that treatment with clarithromycin and ethambutol is not inferior to treatment with clarithromycin, ethambutol, and rifampicin for Mycobacterium avium complex lung disease. Our findings justify a larger clinical trial to compare long-term clinical outcomes for the two treatment regimens. Clinical trial registered with http://www.umin.ac.jp/english/ (UMIN000002819).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 18 publications
5
59
0
1
Order By: Relevance
“…In addition, one patient developed macrolide-resistant MAC-LD after antibiotic treatment for M. massiliense lung disease. Previous studies from Japan and the United States showed that macrolide resistance did not develop even in patients with persistent positive sputum cultures after more than 12 months of recommended multidrug antibiotic treatment (48,49). Our previous study found that 17% of patients with an unfavorable microbiologic response after 12 months of multidrug antibiotic therapy developed macrolide resistance (19).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, one patient developed macrolide-resistant MAC-LD after antibiotic treatment for M. massiliense lung disease. Previous studies from Japan and the United States showed that macrolide resistance did not develop even in patients with persistent positive sputum cultures after more than 12 months of recommended multidrug antibiotic treatment (48,49). Our previous study found that 17% of patients with an unfavorable microbiologic response after 12 months of multidrug antibiotic therapy developed macrolide resistance (19).…”
Section: Discussionmentioning
confidence: 82%
“…Another possible means to increase the AZM C max is to use a two-drug regimen (AZM and EMB) without RIF or with the substitution of other drugs, such as clofazimine, for RIF. A preliminary randomized study showed that the clinical efficacy of a daily two-drug regimen (CLR and EMB) was similar to that of a daily three-drug regimen (CLR, EMB, and RIF) for MAC-LD (39). In addition, the replacement of RIF with clofazimine and daily treatment with CLR or AZM, EMB, and clofazimine achieved similar treatment outcomes in patients with MAC-LD in two retrospective studies (40,41).…”
Section: Discussionmentioning
confidence: 94%
“…The scientific evidence base for most recommendations is narrow and is largely derived from retrospective cohort studies, drug susceptibility surveys, or animal experiments [100,101,102]. Only one prospective, placebo-controlled clinical trial on pulmonary infections caused by MAC is available, which compares the treatment outcome of pulmonary MAC infection with and without additional aminoglycoside in addition to the standard treatment regimen [103].…”
Section: Managementmentioning
confidence: 99%